Differences in the gene transcription state of Botrytis cinerea between necrotic and symptomless infections of lettuce and Arabidopsis thaliana. (16th July 2018) - Emmanuel, C. J.; van Kan, J. A. L.; Shaw, M. W.
Abstract : Botrytis cinerea can establish long‐lived, symptomless, systemic infections in plant species. It is unclear how the fungus colonizes plant tissues without causing tissue damage and necrosis. Three hypotheses are: (i) the fungus state is similar in the two forms of infection, but the plant defences are more effective, leading to multiple small quiescent centres; (ii) excreted molecules that would trigger plant defences are suppressed; (iii) signal exchanges occur avoiding both extensive host cell death and complete spatial restriction of the pathogen. These hypotheses were tested by comparing transcript levels of a set of B. cinerea genes between symptomless and necrotizing infections. Four genes were analysed that participate in signalling pathways required for virulence, as well as five genes that directly participate in causing host cell death or degrading plant cell wall polysaccharides. In lettuce, necrotic infections on detached leaves (12–48 h after inoculation) had similar gene expression patterns to necrotic infections on leaves 44 days after inoculation of the seedlings. Symptomless infections on leaves that expanded after inoculation of young seedlings had similar fungal gene expression patterns at 14, 24 and 34 days after inoculation, which clearly differed from those in necrotizing infections. In Arabidopsis thaliana, there were differences in gene expression patterns between droplet inoculations on leaves, resulting in necrotic lesions, and symptomless infections in stems and leaves. The fungal gene expression patterns differed in detail between lettuce and A. thaliana . The observations suggest that the physiological state of B. cinerea during symptomless infection is distinct from necrotizing infections.